Sintesis dan Uji Fotostabilitas Kompleks Zn(II)-Astaxanthin - Winda Rahmalia; Dwi Imam Prayitno; Adhitiyawarman; Septiani (Jurnal Riset Kimia, 2023)
Astaxanthin is a pigment from the carotenoid group found in algae, shrimp, and crabs. Due to its chemical structure, astaxanthin has many health benefits but low stability against direct exposure to light and oxygen. In this study, the Zn-astaxanthin complex was synthesized using a reflux reactor at 37o and 60oC. Complex compounds were analyzed using a UV-Vis spectrophotometer and FTIR. The UV-Vis spectrophotometer analysis showed a bathochromic shift in acetone (475 to 477 nm). In comparison, in dimethyl sulfoxide, a hypsochromic shift (493 to 475 nm) was observed, and a new absorption peak was observed at 330 nm. FTIR analysis shows a decrease in the intensity of the C=O stretching vibration and -OH group vibration at 1712 and 1219 cm-1, respectively. This indicated an interaction between the metal ion Zn2+ and astaxanthin. Zn-astaxanthin has better stability than astaxanthin during irradiation, using a halogen lamp at a light intensity of 300 W/m2 for 6 hours. Based on the zero-order degradation kinetics model, the degradation rate constant of the Zn-astaxanthin complex was 0.0621, smaller than that of astaxanthin (0.0880).